1996
DOI: 10.1016/0029-7844(95)00356-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cystic Fibrosis Mutations in Pregnancies With Fetal Echogenic Bowel

Abstract: Our results suggest that ultrasonographic detection of fetal echogenic bowel is not associated with an increased prevalence of cystic fibrosis mutations in pregnancies at low risk for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Hence numerous conflicting suggestions for management of this ultrasonographic finding have been advocated by different authors. Sepulveda et al [17] did not find an association between FEB and an increased incidence of CF mutations in 45 pregnancies at low risk for this disease. In contrast, in a review of 357 published cases, Bahdo-Singh et al [5] found CF mutations in 25.6% of cases with FEB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence numerous conflicting suggestions for management of this ultrasonographic finding have been advocated by different authors. Sepulveda et al [17] did not find an association between FEB and an increased incidence of CF mutations in 45 pregnancies at low risk for this disease. In contrast, in a review of 357 published cases, Bahdo-Singh et al [5] found CF mutations in 25.6% of cases with FEB.…”
Section: Discussionmentioning
confidence: 99%
“…These include chromosomal abnormalities, CF, congenital infection, IUGR, fetal anomalies, IUFD, preterm deliveries, gastrointestinal obstruction and/or perforation not associated with CF [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Intra-amniotic bleeding has recently been pointed out as a possible cause for FEB [15][16][17]. It is not clear, however, why FEB is found in association with vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Before CF mutation screening was available for the general population the first groups that were offered testing, in the early 90s, were relatives of patients and partners of recognized carriers [38,39]. Carrier testing was also indicated in cases of couples undergoing IVF due to male infertility and in cases of pregnancy with sonographic echogenic bowel findings during the 2 nd trimester [40,41]. In the late 90s carrier screening for CF started being available for the general population and was offered mainly to couples considering having a child or at the early stages of an ongoing pregnancy [35].…”
Section: Carrier Screening: the Early Years -The First Guidelinesmentioning
confidence: 99%
“…The ultrasound finding of echogenic bowel, present in 0.1 to 0.2% of all pregnancies, may result from fetal meconium ileus and can be due to CF [Dicke and Crane, 1992;Sepulveda et al, 1996;Irish et al, 1997]. The differential diagnosis associated with echogenic bowel also includes a normal pregnancy, chromosome abnormality, and congenital viral infection [Sepulveda et al, 1996].…”
Section: Introductionmentioning
confidence: 98%